Expression and interaction of AGPase subunits reveal functional enzyme complexes in barley - Cheng, Zhenbin; Xi, Boai; Gao, Yan; He, Xudong; Gao, Jianhao; Tang, Haonan; Liu, Yajie; Zhao, Hui; Feng, Zongyun; Yu, Guowu (Frontiers in Plant Science, 2025)
In the starch biosynthetic pathway of Poaceae plants, ADP-glucose pyrophosphorylase (AGPase) serves as the rate-limiting enzyme that catalyzes the conversion of glucose-1-phosphate (G1P) and ATP to ADP-glucose, the immediate precursor for starch synthesis. Despite its fundamental role, the molecular characteristics and regulation of AGPase in barley (Hordeum vulgare L.) remain poorly understood. This study systematically investigated the expression dynamics during barley grain development and subunit interactions of AGPase in vitro. Our findings revealed distinct spatiotemporal expression patterns among AGPase, with preferential accumulation during late grain-filling stages. Co-immunoprecipitation coupled with mass spectrometry (Co-IP/MS) demonstrated specific physical interactions between small (AGPS) and large (AGPL) subunits, confirming the heterotetrameric architecture of functional AGPase complexes in barley. Enzymatic characterization showed that particular subunit combinations (AGPS1-AGPL1 and AGPS2b-AGPL2) exhibited significantly higher catalytic activity compared to other permutations. These results demonstrate that AGPase expression is developmentally regulated, specific inter-subunit interactions determine enzymatic efficiency, and optimal activity requires precise stoichiometric assembly. The demonstrated spatiotemporal coordination of AGPase subunits provides mechanistic insight into the control of starch biosynthesis during the late stage of grain filling. These results also provide a potential key target to improve barley starch synthesis and metabolism.